2021
DOI: 10.1021/acs.jnatprod.1c00662
|View full text |Cite
|
Sign up to set email alerts
|

Strobiloscyphones A–F, 6-Isopentylsphaeropsidones and Other Metabolites from Strobiloscypha sp. AZ0266, a Leaf-Associated Fungus of Douglas Fir

Abstract: Six new 6-isopentylsphaeropsidones, strobiloscyphones A–F (1–6), and a new hexadecanoic acid, (2Z,4E,6E)-8,9-dihydroxy-10-oxohexadeca-2,4,6-trienoic acid (7), together with sphaeropsidone (8) and its known synthetic analogue 5-dehydrosphaeropsidone (9) were isolated from Strobiloscypha sp. AZ0266, a fungus inhabiting the leaf litter of Douglas fir (Pseudotsuga menziesii). The structures of 1–7 were established on the basis of their high-resolution mass and 1D and 2D NMR spectroscopic data, and their relative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…This suggestion was further confirmed by 13 NMR and HSQC spectral data of 2 (Table 1) that revealed relatively shielded carbon resonances at δ C 60.0, 64.2, 63.5 and 63.1 assigned to C-4, C-5, C-6 and C-9, respectively, compared to their counterparts in 1. The obtained results and by comparison with those reported of ambuic acid analogues [3][4][5][6] and conduritols, [7,8] compound 2 was suggested to have an epoxide ring formed over C-4 and C-5 accounting for the additional degree of unsaturation. Further confirmation of the suggested structure of 2 (Figure 1) was provided by 1 H-1 H COSY and HMBC spectra (Figure 2).…”
Section: Characteristics Of the Producer Strainsupporting
confidence: 63%
See 1 more Smart Citation
“…This suggestion was further confirmed by 13 NMR and HSQC spectral data of 2 (Table 1) that revealed relatively shielded carbon resonances at δ C 60.0, 64.2, 63.5 and 63.1 assigned to C-4, C-5, C-6 and C-9, respectively, compared to their counterparts in 1. The obtained results and by comparison with those reported of ambuic acid analogues [3][4][5][6] and conduritols, [7,8] compound 2 was suggested to have an epoxide ring formed over C-4 and C-5 accounting for the additional degree of unsaturation. Further confirmation of the suggested structure of 2 (Figure 1) was provided by 1 H-1 H COSY and HMBC spectra (Figure 2).…”
Section: Characteristics Of the Producer Strainsupporting
confidence: 63%
“…Based on the obtained results, compound 4 was deduced to incorporate a cyclohexenone moiety in its structure. A literature search of 4 revealed its structural resemblance to strobiloscyphones [4] and pestallic acids. [5] Further confirmation to the suggested structure of 4 was provided by HMBC spectrum (Figure 4 2, Figure S41) revealed two unprotonated carbon atoms, a carbonyl carbon at δ C 167.9 and an olefinic carbon at δ C 134.2 in addition to five protonated olefinic carbon atoms at δ C 118.7, 122.9, 133.9, 137.5 and 139.7 that account altogether for four degrees of unsaturation.…”
Section: Characteristics Of the Producer Strainmentioning
confidence: 99%
“…sPLS was sensitive to outliers; results focused on a cluster of Green Trail samples with high elevation and longitude, shown in the top cluster of Figure 4. Analysis revealed the cluster included the post-fire pioneer fungus Pyronema [6,39], Tremella, and Strobiloscypha, which produce strobiloscyphone antimicrobials [40]. Chlorellales algae, toxic Leptiota, and potentially pathogenic Fusarium sequences were elevated.…”
Section: Resultsmentioning
confidence: 99%
“…AZ0266 ( Sarcosomataceae , Pezizales ) collected from surface-sterilized decomposing leaf litter of Douglas fir ( Pseudotsuga menziesii ). 40 It was shown that sphaeropsidone reduced Candida albicans growth at concentrations above 50 μg mL −1 , but no MIC values were detected at these concentrations. The authors noted that sphaeropsidone was less active in the antifungal assay than its 1,4-dione analogue.…”
Section: Epoxyquinolsmentioning
confidence: 99%
“…AZ0266 ( Sarcosomataceae , Pezizales ). 40 Strobiloscypha sp. AZ0266 was isolated from surface-sterilized decomposing leaf litter of Douglas fir ( Pseudotsuga menziesii ), an evergreen coniferous tree of southeastern Arizona.…”
Section: Epoxyquinonesmentioning
confidence: 99%